(untitled) (Latin-American Journal of Computing, 2017)
In this article, we describe the design and implementation of an experimental robotic hand platform in order to create a real environment to tests signals that have been treated with different applied techniques or devices used in the extraction of bioelectrical signals. Mechanically the platform has a hand of 5 degrees of freedom, one for each finger. The movement of each finger is generated by a servomotor, which receives the signal from an electronic distribution board. The reception of signals from the outside is both wired and wireless. To check the individual movement of the fingers, a joystick, a keyboard and Bluetooth device have been provided. The movement of the joints on each finger is achieved by tightening a nylon thread from the pulley located on the servomotor shaft. PWM signals were used to check the movement of the fingers.